Academic Stress and Parental Pressure as Predictors of Psychological Health in Covid-19 Emergency Times among School Children with Intellectual Disabilities in Calabar Metropolis, Cross River State, Nigeria: The Implication for Counseling - Unwada, Ekpang Pauline; Cklaimz, Enamhe Dorn; Awhen, Opoh Fredrick; Okpeche, Philip; Rose A., Undie; Ogar, Odey Edward; Obanye E., Bassey; Beshel, Unimna; Odey, Mboto Akomaye; Nwafor, Patrick Ifeanyi; Edwin, Effiom John; George, Ekuri Patrick; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: Academic stress and parental pressure have been shown to be important factors associated with psychological health. However, the internal mechanism between them is still not clear. Aim: This study assessed the joint significant influence of the predictor variables (academic stress and parental pressure) as predictors of psychological health in COVID-19 emergency times among school children with disabilities in Calabar metropolis, Cross River State, Nigeria: The implication for counseling. One study objective was stated, and one statement of hypothesis was posed. A literature review was carried out based on the variable under study. Method: The research design that was adopted in this study is correlational research design. A simple random sampling technique was adopted to select the 234 respondents sampled for the study from a population of 2,344. A validated 35-item four-point modified Likert scale questionnaire was the instrument used for data collection. The face and content validity of the instrument was established by experts in Test and Measurement. The reliability estimates 0.89 of the instruments were established using the Cronbach Alpha method. A multiple Linear regression statistical tool was used to test the hypotheses formulated for the study. The hypothesis was tested at a 0.05 level of significance. Results: The results obtained from the data analysis revealed that there is a joint significant influence of the predictor variables (academic stress and parental pressure) on psychological health in COVID-19 emergency times among school children with learning disabilities. Conclusion: Sometimes, stress and pressure can be motivating at the mild stage. However, at the severe stage, it could lead to frustration, social pressure, family workload, and cognitive overload, which in turn influences an individual to use and abuse substances in order to escape from unpleasant feelings of life situations. It was recommended that Parents should advise students on how to perform well academically rather than setting standards that may put so much pressure on students, which may have a negative impact on the psychological health of the students.